Esophagogastric malignancies detected in a tertiary surgical center endoscopy unit from Turkey: a descriptive study - UreyenOrhan; Mehmet MeralUlvi; UzMurat; IlhanEnver (中国普通外科杂志, 2017)
Background: The most common symptoms of upper gastrointestinal (UGI) diseases are epigastric pain and heartburn, nausea and vomiting, regurgitation and dysphagia. Endoscopic examination is the most reliable method for assessing UGI evaluation. Methods: Malignant tumors detected in UGI endoscopies performed between Dec 31, 2015 and Jan 1, 2011 were included in our study. Age, gender, indication for endoscopy, tumor site, tumor type, stage of disease and type of treatment data were recorded. Results: According to the analysis of five-year patient data; 39 (1.17%) of 3,309 cases had malignancy in the UGI endoscopy. The average age of malignancy detected cases were 63.4 years (range, 33–88 years). In the malignancy positive group; 35 (1%) cases had gastric and 4 (0.12%) cases had esophagus tumors. According to the gastric localization of tumors, 12 of cases were distal, 10 were proximal, 7 were middle and 4 were linitis plastica. Two of the cases had previous gastric surgery and the gastric malignancy of these cases was localized at the gastrojejunostomy site. The most frequent symptoms were abdominal pain, anemia, dyspepsia, bleeding, weight loss, obstruction and dysphagia in patients with gastric cancer. Two (5.7%) of the cases had previous gastrectomies because of benign causes. Malignant tumors were detected in the remnant tissue of these cases. The percentage of over 50-year-old patients was 89.7% in UGI malignancy detected patients. Three percent of gastric cancers were stage I, 18% of them were stage II, 25% of them were stage III and 53% of the cases were stage IV. Seventy-five percent of esophageal cancer cases had systemic metastases. Conclusions: Malignity is rarely detected among the patients from general surgery outpatient clinic, on whom UGI endoscopy is performed. But it is not different from the literature. Most of the malignancies are at advanced stage. In older age patients, endoscopy should be recommended even there are nonspecific symptoms. In the presence of alarm symptoms, UGI endoscopy should be recommended without considering the age.